Evaluation of Histopathology Findings of Clinically Confirmed Psoriasis Vulgaris - Sawitri; Fadila, Arisia; M. Yulianto Listiawan; Priangga Adi Wiratama; Dwi Murtiastutik; Evy Ervianti; Linda Astari; Damayanti; Diah Mira Indramaya; Afif Nurul Hidayati; Medhi Denisa Alinda (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Psoriasis vulgaris can be diagnosed clinically. A biopsy is usually used to confirm non-classic cases. The findings of the histopathology feature are not usually present, thus clinical relevance is needed to confirm the diagnosis. Purpose: To describe the histopathology findings from tissue samples of histopathologically confirmed psoriasis vulgaris reported in the Department of Pathology and Anatomy of Dr. Soetomo General Hospital. Methods: A descriptive-retrospective study of pathology-ascertained tissue samples of histopathologically confirmed psoriasis vulgaris was reported in the Department of Pathology and Anatomy from patients who were also previously diagnosed clinically with psoriasis vulgaris in the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital over a period of 2 years. Morphological parameters were observed after histopathology sections were stained with hematoxylin and eosin. Result: Thirty-three tissue samples were examined. Parakeratosis (86%) and hypogranulosis (70.3%) were the most observed findings. Club-shaped rete ridges, suprapapillary plate thinning, and spongiform pustules of Kogoj were the least observed findings (each by 2.7%). Three tissue samples (8.1%) showed only parakeratosis. Only 1 tissue sample (2.7%) showed 4 features (absence of the granular layer, parakeratosis, microabscess of Munro, and spongiform pustules of Kogoj). No tissue sample showed every histopathology finding of psoriasis vulgaris. Conclusion: All of the histopathology features of psoriasis vulgaris are rarely found in one tissue section. Albeit histopathology is believed to be the gold standard diagnosis of psoriasis vulgaris, relevance with clinical findings is still mandatory to support the diagnosis.